Support for ICT entrepreneurs to match each need - Flouvat, Catherine (Technical Centre for Agricultural and Rural Cooperation, 2016)
French mobile phone provider Orange has developed several support programmes for ICT start-ups in Africa and the Middle East. By providing the right, tailor made support facilities it aims to enable a home-grown e-agriculture sustainable growth model for innovative, young entrepreneurs.